PENGEMBANGAN E-BOOKLET IDENTIFIKASI LICHEN DI TEPIAN SUNGAI DESA MAWANGI KABUPATEN HULU SUNGAI SELATAN SEBAGAI MATERI PENUNJANG MATA KULIAH CRYPTOGAMAE - Rahmawati Rahmawati; Sri Amintarti (Bioedukasi Jurnal Pendidikan Biologi, 2026)
Lack of digital-based teaching materials and local potential on lichen material that is considered difficult to understand by students so that it can be developed into e-booklet teaching materials. This study aims to identify lichen on the banks of the Mawangi Village river, Hulu Sungai Selatan Regency, and the suitability, feasibility, readability, and effectiveness of the e-booklet developed as supporting material for the Cryptogamae course. Data collection used an exploration method with a 4D development model. The subjects of the suitability and feasibility test consisted of 2 validators. The subjects of the readability test consisted of 9 students and the effectiveness of students consisted of 17 students. The results of the study showed that 16 species of lichen were found on the banks of the Mawangi Village river, namely Graphis scripta, Phyxine sp, Lepraria sp, Diorygma sp, Leptogium sp, Cryptothecia striata, Verrucaria baldensi, Candelariella vitellina (Hoffm.) Mull.Argh., Herpothalllon rubrocinctum, Bacidia schweinitzii, Parmotrema perlatum, Syncesia leprobola, Chrysothrix candelaris, Bacisia viridifarinos, Dyplolabia afzelii, and Graphis sp. The developed e-booklet product received an average score of 4.29 for the suitability test with the very suitable category, 4.35 for the feasibility test with the very feasible category, 4.49 for the readability test with the very good category, and 0.81 for the effectiveness test with the high category. These results indicate that this e-booklet is suitable for use as supporting material in the cryptogamae course.Kata kunci: E-booklet, lichen, model pengembangan 4-D, penunjang mata kuliah Cryptogamae.